2009
DOI: 10.1002/cb.278
|View full text |Cite
|
Sign up to set email alerts
|

Exploring memory for product names advertised with humour

Abstract: Three studies explored the effects of humour in advertising on brand name memory. Study 1 showed that humour impaired memory for products but enhanced memory for advertisements. Study 2 showed that brands that had been promoted in humorous advertisements were less accessible in memory than brands promoted in non-humorous advertisements. Study 3 separated conscious and unconscious memory components with the process-dissociation procedure 1 week after the ad exposure. The memory-reducing effect of humour was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…These ideas were confirmed by one of our studies (Hansen, Strick, Van Baaren, Hooghuis, & Wigboldus, 2009, Study 1). We presented participants with a questionnaire that contained pictures of characteristic scenes of humorous and non-humorous (control) ads that were frequently broadcast on TV at the time.…”
Section: Empirical Evidence For the Model Explicit Versus Implicit Brsupporting
confidence: 84%
“…These ideas were confirmed by one of our studies (Hansen, Strick, Van Baaren, Hooghuis, & Wigboldus, 2009, Study 1). We presented participants with a questionnaire that contained pictures of characteristic scenes of humorous and non-humorous (control) ads that were frequently broadcast on TV at the time.…”
Section: Empirical Evidence For the Model Explicit Versus Implicit Brsupporting
confidence: 84%
“…For example, experimental participants were more likely to remember humorous sentences than nonhumorous sentences when both types of sentences were in the same list (Schmidt 1994). Another study consistently found that although ads themselves are easier to remember when they are humorous, consumers were less likely to remember the product in humorous ads than in nonhumorous ads (Hansen et al 2009). In sum, although integral humor appreciation improves memory, incidental humor appreciation tends to hurt memory because humorous content distracts consumers from nonhumorous information.…”
Section: Humor Appreciation Influences Decision Makingmentioning
confidence: 96%
“…Because the efficiency of preventive health campaigns depends at least on individuals' tendency to counterargue the underlying persuasive messages, the use of humor could be a good strategy as long as humor is directly linked to the central message (for evidence that humor unrelated to the central message can be distracting, see Hansen et al, 2009;Strick, Holland, van Baaren, & van Knippenberg, 2010a). To critically assess the contribution of humor in health communication, we conducted two experiments in which we compared humorous and nonhumorous preventive health ads.…”
mentioning
confidence: 99%